Study On Determinants Of Online Shopping In Malaysia - Chua, Adeline Phaik Harn (2005)
This study mainly intends to investigate factors, which influence online purchases among Malaysian Internet users. Based on a survey sample of 215 Internet users, this study also explores their information-seeking patterns as their motivations and concerns for online shopping.